Bi5Te3 superlattices as a cathode material for aqueous zinc-ion battery - Bakavets, Aliaksei S.; Ragoisha, Genady A.; Aniskevich, Yauhen M.; Streltsov, Eugene A. (Journal of the Belarusian State University. Chemistry, 2023)
A prototype of the aqueous zinc-ion battery which uses in the discharge stage the underpotential deposition with charge transfer of Zn2+ ions to Zn adlayer on electroactive material has been developed. The cathode material was (Bi2)m(Bi2Te3)n superlattice with the composition corresponding to Bi5Te3. The charge transfer in the cathode during battery charging and discharging is characterised by cyclic voltammetry, electrochemical impedance spectroscopy and galvanostatic charge and discharge curves recording. The presence of bismuth nanolayers in the superlattice ensures efficient charge transfer in the cathode material, while bismuth telluride layers accept Zn2+ ions with the formation of adatomic zinc layers, the latter are oxidised anodically during battery charging.